Deficient humoral responses and disrupted B-cell immunity are associated with fatal SFTSV infection - Peixin Song (Nature Portfolio, 2018)
SFTSV is a novel phlebovirus associated with high fatality, but understanding of pathogenesis is lacking. Here the authors show defective cellular immunity, deficient antibody production and defunct humoral immunity is associated with fatal infection in human cases of infection.